(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the thickness of the maxillary sinus lateral wall on cone-beam computed tomography in Vietnamese adults according to sex, side, and tooth region, and to assess its relationship with age and the diameter of the posterior superior alveolar artery. Materials and methods: A cross-sectional descriptive study was conducted on 200 cone beam computed tomography scans (400 maxillary sinuses) of patients aged 18-65 years. Maxillary sinus lateral wall thickness was measured at 3 mm, 10 mm, and 15 mm above the sinus floor at posterior maxillary tooth regions (first and second premolars, first and second molars). Differences according to sex, side, and tooth region were analyzed, and correlations with age and posterior superior alveolar artery diameter were assessed. Results: The mean maxillary sinus lateral wall thickness at 3 mm, 10 mm, and 15 mm above the sinus floor was 1.67 ± 0.46 mm, 1.25 ± 0.36 mm, and 1.38 ± 0.45 mm, respectively, with the thinnest wall observed at the 10-mm level. Maxillary sinus lateral wall thickness was generally greater in males than in females, with statistically significant differences at premolar and second molar regions (p < 0.05), while no significant difference was observed at the first molar region. Significant differences in maxillary sinus lateral wall thickness were found among tooth regions (p < 0.05), with the thinnest wall at the premolar area. No significant correlation was observed between maxillary sinus lateral wall thickness and age (p > 0.05). A weak positive correlation between maxillary sinus lateral wall thickness and posterior superior alveolar artery diameter was detected at the 3-mm level (r = 0.331; p < 0.05), but not at the 10-mm or 15-mm levels. Conclusion: The maxillary sinus lateral wall in Vietnamese adults is relatively thin, particularly in the premolar region, which is commonly selected for lateral window sinus floor elevation. The relationship between maxillary sinus lateral wall thickness and the posterior superior alveolar artery is evident only near the sinus floor. Preoperative cone beam computed tomography assessment of the lateral wall and related vascular structures is essential to minimize surgical complications.